TINGKAT KESULITAN, DAYA BEDA, DAN RELIABILITAS TES IPAS KELAS 5 SEMESTER GANJIL - Gumelar, Agus; Bahrudin, Ahmad; Alhafid, Ahmadfalih; Diyahpangesti, Alfrida; Abdulrohman, Alfin; Suwarto, Suwarto (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims to: (1) explain the item difficulty of the odd semester class 5 science test items, (2) explain the item Discrimination of odd semester class 5 test items, (3) determine the reliability of the odd semester class 5 test. The IPAS test consists of 10 questions and was tested on 188 respondents. The data analysis technique used is the item program version 3.00. The results of the analysis show: (1) The item difficulty for class 5 odd semester ranges from 0.23 to 0.64. The level of difficulty of the most difficult item is item 10 and the level of difficulty of the easiest item is item 5. The ratio of the percentage of medium items: difficult items is 90%:10%, (2) Differentiation of grade 5 science test items for odd and even semesters ranges from 0.30 to 0.55. The lowest differentiating power is item 1 and the highest differentiating power is item 7. There are 0 items that have a bad difference. There are only 5 items that have different power. There are 5 items that have good item differentiation. There are 0 items that have very good item differentiation, (3) The reliability of the odd semester 5th grade science test is 0.9.